Solar radiation map of Jordan governorates - S. Alrwashdeh, Saad; M. Alsaraireh, Falah; A. Saraireh, Mohammad (International Journal of Engineering and Technology, 2018)
The solar energy potential in Jordan is enormous as it lies within the solar belt of the world with average solar radiation between 4 and 8 KWh/m2, which implies a potential of 1400-2300 GWh per year annually. Electricity demand in Jordan plays a significant role in the high amount of energy consumption to cover the needs of heating, cooling, lighting, etc. For that, the availability of the solar radiation infor-mation becomes essential to help in the design and building of the solar energy application. In this study, a solar radiation map is provided of all Jordan governorates.Â